Impact of varying protein sources and ammonium chloride inclusion on feedlot goat growth and carcass traits - Gauthier, Addison P.; Sorensen, Rachel J.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
The purpose of this experiment is to study the effects of different protein sources (dried distiller grains and SoyPlus) and acid sources (ammonium chloride and SoyChlor) on the weight and carcass composition of feedlot goats. Our hypothesis was that the replacement of DDGS with SoyPlus and the replacement of NH4Cl with SoyChlor would have a positive impact on weight gained, carcass quality, and the pH of the goat urine as well as result in a reduced feed cost. Seventy-five boer goat kids all relatively the same age and weight were used in a randomized design. Animals were housed at the Kansas State University Sheep and Meat Goat Center with three boar goats per pen (five pens per treatment). The pens were then allotted to one of five different diets: 1) 18.7% soy bean meal with .75% NH4Cl; 2) 34.4% DDGS with .75% NH4Cl; 3) 22.0% SoyPlus with .75% NH4Cl; 4) 17.2% SBM with 4.83% SoyChlor; and 5) 20.0% SoyPlus with 4.83% SoyChlor. These diets were fed in an open feeder, allowing the goats to consume the feed whenever they chose to. The feed was a pelleted diet made at the Kansas State University Feed Mill and all goats had access to clean, fresh water at all times. The diets were fed for 42 days with goat weights and feeder weights measured once a week, every week. Feed added was measured whenever feed was placed in the feeders throughout the weeks of the trial. Once the trial was completed, the largest and the smallest goat of each pen were slaughtered allowing carcass data to be collected. We calculated average daily gain, average daily feed intake, and feed efficiency to help establish a conclusion that SoyPlus and SoyChlor products did not have a noticeable effect on the goats ADG (P > 0.3) when compared to the other feeds tested.
Keywords: Fall 2018